أصحاب أبي الحسن الشاذلي "الأربعين" في المغرب والمشرق - قموح,فريد; بكيز بحاز,ابراهيم (University of Eloued جامعة الوادي, 2024)
إن المتتبع لسيرة القطب أبي الحسن الشاذلية الأب الروحي للطريقة الشاذلية تستوقفه محطات أساسية لا يمكن التغاضي عنها أو إغفالها نظرا لما تركته من أثر بارز استمر طوال حياته وبخاصة في مرحلة مكوثه الطويل بتونس وكذا مرحلة استقراره بمصر حتى وفاته، ثم استمر ذلك الأثر أكثر إشراقا بعد وفاته، ونخص بالذكر في هذا المقام مسألة أصحابه "الأربعين" في المغرب والمشرق الذين رافقوه أثناء مساره الطويل في تكوين شخصيته الصوفية، من البحث عن الحقيقة حتى الارتقاء إلى مصاف القطبانية، وما ترتب عن ذلك من تراث كانوا شهودا عليه، ثم ساهموا في تعريف الناس به ونشره في الآفاق، ومازال صدى مجهوداتهم يُلْتَمس إلى اليوم. لقد شغل أصحاب الشيخ أبي الحسن جزء هاما في حياته بعلاقاتهم وخدمتهم ودفاعهم وحضورهم الدائم، وذلك لما مثلته الصحبة عند الشاذلي من مظهر التفاعل الايجابي للقائد الصوفي مع المجتمع بفئاته، ومظهرا لقوة الرابطة الروحية والثقة المتينة بينه وبين أتباعه، وسبيلا لاستمرار شعاعه العلمي والسلوكي سواء في حياته أو بعد مماته، ومن دلالات ذلك قول الشاذلي "كتبي أصحابي"، وذلك رد قوي مفعم بارتياح عن دور أصحابه الثابت في نشر أفكاره وحفظها وتبليغها للناس، وهذا ما يدفعنا لطرق هذا الموضوع من جوانبه المختلفة كحقيقة وجودهم وعددهم ودورهم وغيرها. The follower of the biography of Abu Al-Hassan Al-Shadili, the spiritual father of the Shadili method, is stopped by basic station that cannot be overlooked, given the prominent impact he left that continued throughout this life, especially during the period of this long stay in Tunisia, as well as the stage of this stability in Egypt until his death, and then that impact continued brighter after his death. We mention in this respect the issue of his companions in the Maghreb and the East who accompanied him during his busy path in the formation of his sufi personality, from the search for the truth until the elevation to the ranks of the quatbaniyyah, and the resulting heritage that they were witnesses to, and then they contributed to introducing people to him and publishing him in prospects, and their efforts are still echoed today. Shadili„companions occupied an important part in his life with its relations, service, defense, and permanent presence, and that is because companionship for Al-Shadili represented the manifestation of the positive interaction of the sufi leader with the community of its groups, and an affirmation of the strength of the spiritual bond and the solid trust between him and followers and a way for the continuation of its scientific and behavioral ray in his life and after his death. Among the indications of this is Al-Shadili saying: “My books are my companions”, and that is a strong response full of satisfaction about the constant role of his companions in spreading his ideas, preserving them, and informing them to people
Keywords: الشّاذلي; الأصحاب; المغرب; المشرق; الأربعين; Al-Shadili; The Companions; Maghreb; East; The Forty; Al-Sheikh